Digitonthophagus gazella auctorum: an unfortunate case of mistaken identity for a widely introduced species (Coleoptera: Scarabaeidae: Scarabaeinae: Onthophagini) - Génier, François; Davis, Adrian L.v. (Zootaxa, 2017)
At risk of committing entomological heresy, we question the identity of a dung-burying beetle species that originates from Africa and has been introduced first into Hawaii and subsequently to Australasia, North America, and South America (Fincher 1986; Edwards 2007; Noriega et al. 2010) for pasture improvement and biological control of dung-breeding flies (Waterhouse 1974; Bornemissza 1979). Under the name Onthophagus gazella (Fabricius 1787), it was the first species selected for introduction into Australia by the CSIRO Dung Beetle Project (Bornemissza 1976; Edwards 2007). Firstly, in 1968, a "tropical strain" was introduced from Hawaii where it had become established after introduction from Zimbabwe in 1957 (Markin & Yoshioka 1998). Later, after establishment of the CSIRO Dung Beetle Research Unit in Pretoria in 1970, a "cold" or "even rainfall strain" was introduced into Australia directly from South Africa (Bornemissza 1976) (even rainfall region = south coast of Eastern Cape). The species was subsequently introduced into the southern continental United States of America (Victoria County, Texas) from Hawaii (Montes de Oca & Halffter 1998) then elsewhere into southeastern and southwestern states from Hawaii and breeding colonies from Australia (Anderson & Loomis 1978). It has since expanded its range through Mexico, Central America, and the Caribbean to coastal Colombia (Kohlmann 1994; Noriega 2002; Noriega et al. 2006, 2011). Expansion of its range within central southern South America (Noriega et al. 2010) has been assisted by introductions into Brazil from the United States of America since the 1980s (Bianchin et al. 1998), and others into Venezuela and Chile (Vidaurre et al. 2008). More recently, it has been introduced into quarantine and field trials in New Zealand (Forgie et al. 2013) using individuals originating from the south coast of the Eastern Cape and Northwest Province of South Africa (S. Forgie, personal communication).